Color doppler evaluation of cerebral-umbilical pulsatility ratio and its usefulness in the diagnosis of intrauterine growth retardation and prediction of adverse perinatal outcome - Bano, Shahina; Chaudhary, Vikas; Pande, Sanjay; Mehta, VL; Sharma, AK (Indian Journal of Radiology and Imaging, 2010)
Objective: The aim of our study was to evaluate the usefulness of the pulsatility index (PI) of the umbilical artery (UA) and that of the fetal middle cerebral artery (MCA), as well as the ratio of the MCA PI to the UA PI (C/U ratio), in the diagnosis of small-for-gestational-age (SGA) fetuses and in the prediction of adverse perinatal outcome. Materials and Methods: The study population comprised 90 pregnancies of 30-41 weeks gestation that had been diagnosed clinically as intrauterine growth retardation (IUGR) over a period of 1 year. The UA PI and the MCA PI as well as the C/U ratio were calculated. Results: Of the 90 pregnancies in the study, 24 showed abnormal UA PI. Among these, 21 (87.5%) were SGA and 19 (79.2%) had adverse perinatal outcome. Of the four of the 90 pregnancies that showed abnormal MCA PI, all were SGA and had adverse perinatal outcome. Similarly, of the 20 out of 90 pregnancies that showed abnormal C/U ratio (< 1.08), all 20 (100%) were SGA and had adverse perinatal outcome. The results were correlated with parameters of fetal outcome. Conclusion: Inferences drawn from the study were: (1) The C/U ratio is a better predictor of SGA fetuses and adverse perinatal outcome than the MCA PI or the UA PI used alone, (2) The UA PI can be used to identify IUGR per se and (3) The MCA PI alone is not a reliable indicator for predicting fetal distress.
Keywords: Intrauterine growth retardation; pulsatility index; umbilical artery pulsatility index; middle cerebral artery pulsatility index; middle cerebral artery to umbilical artery pulsatility index ratio